Does childcare improve the health of children with unemployed parents? Evidence from Swedish childcare access reform - Aino-Maija Aalto; Eva Mörk; Anna Sjögren; Helena Svaleryd (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2019)
We analyze how access to childcare affects the health outcomes of children with unemployed parents using a reform that increased childcare access in some Swedish municipalities. While we find no effects of childcare access on hospitalization for 2- to 3-year-olds, our results suggest that 4- to 5-year-olds were more likely to be hospitalized due to infections when they first gained access to childcare. Children aged 10 to 11 years who had access to childcare earlier in their childhood, while their parents were unemployed, were less likely to be prescribed medication for respiratory conditions and allergies. Taken together, our results suggest that the immediate health consequences of childcare access for children of unemployed parents are limited. Our findings support previous evidence that the greater exposure to microorganisms induced by childcare attendance may reduce the risk of developing allergies and asthma.
Keywords: I14; J13; 330; Childcare; Child health; Unemployment; Quasi-experiment